The Effect of Binahong Leaf Extract as a Disinfectant in Duck Egg Incubator - Eulis Tanti Marlina; Ellin Harlia; Yuli Astuti Hidayati (Jurnal Ilmu-Ilmu Peternakan, 2023)
Binahong is a native South American plant that grows well in Indonesia. The active compounds contained in the binahong plant are widely used as traditional medicine. Active compounds such as flavonoids, alkaloids, saponins, triterpenoids, comarins and phenolic acids are antimicrobial. This study aims to determine the antimicrobial effectiveness of binahong leaves in inhibiting bacteria and fungi in duck egg incubators. The concentration of binahong extract used was 30%, 40%, 50%, 100% binahong leaf solution, and 1% chemical disinfectant Cethylpiridium Chloride (CPC). Evaluation was carried out on decreasing the number of bacteria, fungi, inhibition zones on gram-positive and gram-negative bacteria and identification of fungi reduced by binahong leaf extract in duck egg incubators. Data were analyzed using ANOVA and Tukey's test. The results showed the concentration of 50% binahong leaf extract had the option to decrease the number of bacteria and fungi 88.48% and 53.81%, respectively, 100% binahong solution could decrease the quantity of bacteria and fungi 56.75% and 34.95% respectively and 1% CPC chemical disinfectant reduced the number of bacteria and fungi 91.65% and 62.60%, respectively. Binahong leaf extract produced inhibition zones on gram-positive and gram-negative bacteria with a strong interpretation, namely 19.2 mm and 16.2 mm, respectively.